Persepsi Guru Berlatar Belakang Non-Pendidikan Khusus Dalam Mengajar Anak Berkebutuhan Khusus di Sekolah Inklusi SD Gmim Kayawu Tomohon - Yuniarti, Kezia; Dapa, Aldjon N.; Marentek, Lay Keke. M. (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to explore the perceptions of teachers with non-special education backgrounds towards children with special need in the context of inclusive education at SD GMIM Kayawu Tomohon. Inclusive education emphasizes equal access for all children, but is often hindered by teacher readiness and facilities. Using a descriptive qualitative approach with a single case study design, this research involved 7 teachers as informants. Data were collected through in-depth interviews, observations, and documentation, then analyzed using data reduction, presentation, and conclusion, as well as triangulation for validity. The results show that teachers' perceptions evolved from initial negative stereotypes to empathy through direct interaction. Main themes include understanding about children with special need and inclusion; the influences of children with special need on the process of learning and teaching; training and teaching methods; personal experiences and obstacle; teacher role and policy expectations. Perceptions are influenced by internal factors (personal experience) and external factors (school support), in line with Jalaluddin Rakhmat's (2018) theory of perception as a subjective process and interaction